Pendampingan Belajar Anak Berkemapuan Di Bawah Rata-Rata Dusun Sumbersari Kencong Kepung Kediri - Muhammad Yazid Fahmi; Miftahul Arif (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
In every class, the ability of students is always different. Starting from children who have above average abilities than other students, children who have average abilities, and students with below average abilities. This is very common, even before the school entrance test there is screening, there are still students who are ability below average in the classroom. Not only in public schools, in madrassas, boarding schools and other higher educational institutions are also the same. One solution is for a teacher to appoint and accompany students with above average or in average-capable students to participate in improving the abilities of other students who are still below average by helping learn friends who still have below average abilities. What is meant by children who have above average abilities are not children with super IQs, but children who have mastered the lessons that have been and will be conveyed. A teacher is also not only in the companion position, but also instills the nature of sharing knowledge with his peers and instills good morals for those who are more capable of not bragging to friends who still have substandard abilities. Of these average and above-average student participants, at least we as educators are able to reduce the number of children who are capable below average. It would be even better if the number of children who have below average ability disappears altogether.